2020
DOI: 10.3329/bjsir.v55i1.46733
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Salmonella and Escherichia coli in fish farms and markets in Dinajpur, Bangladesh

Abstract: The research work was conducted to assess the incidence of Salmonella and Escherichia coli (E. coli) contamination in different fish farms and fish markets of Dinajpur district of Bangladesh. The level of incidence of Salmonella contamination was greater in scum samples (93.8%) and for E. coli the higher contamination found in water samples (81.3%). The study showed that, water and fish samples were also Salmonella positive and the percentage was 87.5% and 57.8% respectively and for E. coli contamination about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Salmonella is a zoonotic pathogen that can be found in fish worldwide. In this study, the highest prevalence of Salmonella (58.3%) was observed in cultivation water, which was consistency to a previous study in fish pond from Bangladesh (87.5%) (Ava et al, 2020). However, the prevalence of Salmonella in freshwater ranged from 11.9-20.6% (Traoré et al, 2014;Antaki et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Salmonella is a zoonotic pathogen that can be found in fish worldwide. In this study, the highest prevalence of Salmonella (58.3%) was observed in cultivation water, which was consistency to a previous study in fish pond from Bangladesh (87.5%) (Ava et al, 2020). However, the prevalence of Salmonella in freshwater ranged from 11.9-20.6% (Traoré et al, 2014;Antaki et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…High levels of fecal coliforms and E. coli in fish can suggest poor water quality in the production area. The contamination of E. coli in fish is assumed a higher risk of pathogenic bacteria contamination than those fish did not contamination (Ava et al, 2020). Among different types of tilapia sample, including meat, intestine, and gill, the highest concentration of fecal coliform was found in gill (3.0 ± 0.67 × 10 3 CFU/g), whereas the highest concentration of E. coli was found in intestine (1.45 ± 0.19 × 10 3 CFU/g) of tilapia area (Mandal et al, 2009).…”
Section: Distribution Of Bacteria In Tilapia Aquaculture Fecal Colifo...mentioning
confidence: 99%
“…The presumption of Salmonella in the samples requires special attention. Ava et al [29] found high contamination of fish by Salmonella (57.8%) in their study.…”
Section: Discussionmentioning
confidence: 70%
“…Similar to a recent study (Ava et al . 2020), the higher copy number of E. coli , Shigella and S. enterica may have a link to water use for cleaning and basket to hold fish in the market. The frozen fish in the supermarket usually undergone an extra step of hygienic cleaning and processing and that might remove some bacteria before freezing.…”
Section: Resultsmentioning
confidence: 99%